Potensi Olahraga River Tubing Sebagai Strategi Penggembangan Pariwisata Olahraga di Kabupaten Karawang - Dhika Bayu Mahardhika; Astried Milla Cahaya; Attahariq Muhammad; Baghea Hatelega; Bintang Yogie Ramdhana; Bryan Nurbagja Permana (Peneliti.net, 2023)
From time to time, sports are growing, lots of people enjoy sports activities, especially traditional sports. At present sports are widely used by several sectors to develop, including the tourism sector. The purpose of this service activity is to attract the interest of the community in sports tourism, especially water sports, namely river tubing. The participants who took part in this activity were 15 participants from the surrounding community who are near the tourist attractions of Imah Urang. As well as involving PJKR 2019 B students as committee members. The supervisor for this activity came from a PJKR FKIP lecturer at Singaperbangsa Karawang University, the location of the activity was in Klari, East Karawang, Karawang Regency. The results of the activity show that 100% gave a very good response and really liked the activity.